2004
DOI: 10.1002/jmri.20184
|View full text |Cite
|
Sign up to set email alerts
|

MRI monitoring of Avastin™ antiangiogenesis therapy using B22956/1, a new blood pool contrast agent, in an experimental model of human cancer

Abstract: Purpose:To evaluate the diagnostic and prognostic potential of a new protein-binding contrast medium, B22956/1, for quantitatively characterizing tumor microvessels by MRI and monitoring response to antiangiogenic therapy. Materials and Methods:Dynamic contrast-enhanced MRI (DCE-MRI) was performed in an experimental cancer model with the use of the novel protein-binding agent B22956/1, a low molecular contrast agent (ProHance™), and a macromolecular contrast medium, albumin-(Gd-DTPA). MDA-MB-435, a human cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 42 publications
5
64
1
Order By: Relevance
“…The effect of an enhanced microvasculature permeability following the antiangiogenic treatment has already been reported in several cases, a process known as vasculature normalization [49]. In fact, our findings are in agreement with recently published data reporting an increase of permeability transfer constant under antiangiogenic treatment by exploiting intermediate MW contrast agents [50,51].…”
Section: Dce-mri Has Been Used In the Last Decades In A Numbersupporting
confidence: 93%
“…The effect of an enhanced microvasculature permeability following the antiangiogenic treatment has already been reported in several cases, a process known as vasculature normalization [49]. In fact, our findings are in agreement with recently published data reporting an increase of permeability transfer constant under antiangiogenic treatment by exploiting intermediate MW contrast agents [50,51].…”
Section: Dce-mri Has Been Used In the Last Decades In A Numbersupporting
confidence: 93%
“…An optimal payload of 22 Gd-DOTA with mal-BSA (Gd-DOTA) 22 showed contrast effects comparable to albumin (Gd-DTPA) 30 , which is used as a standard to evaluate performances of novel intravascular agents. (79)(80)(81)(82) Though further studies are required to evaluate immunogenicity of the agent, the high specificity of mal-BSA (Gd-DOTA) n shows promise for reducing dosage of administration and toxicity compared to high dose nonspecific contrast agents currently employed in the clinic. Future work includes isolating the regional domains of maleylated BSA that afford targeting in order to circumvent immune responses that may be provoked by full length protein.…”
Section: Resultsmentioning
confidence: 99%
“…DCE-MRI measurements showed that after just 2 days patupilone significantly decreased the rBVol (P = 0.0005). Other vascular variables, such as vessel permeability and overall perfusion, were unaffected, a distinct difference in vascular response in comparison with therapies that target vascular endothelial growth factor (24,37) or the vascular endothelial growth factor receptor (33) or the endothelial cells directly (38,39) and not necessarily expected given that other antivascular/disruptive therapies can decrease permeability and/or perfusion (9,40). Vascular casts of tumors made 2 days after treatment showed a trend for patupilone to induce a decrease in blood vessel mass, and at this time point, the tumor IFP was also decreased (P = 0.02).…”
Section: Discussionmentioning
confidence: 99%